2015
DOI: 10.1007/s10826-015-0248-x
|View full text |Cite
|
Sign up to set email alerts
|

Negative Affectivity Moderates Associations Between Cumulative Risk and At-Risk Toddlers’ Behavior Problems

Abstract: This study examined cumulative risk, temperament traits, and their interplay as predictors of internalizing, externalizing, and sleep problems in at-risk toddlers. Participants were 104 low-income mother-toddler dyads recruited from Women, Infants, and Children (WIC) sites in a large city. The sample was primarily African American, and mothers were 21 years of age or younger at the child’s birth. The dyads were assessed when the toddlers were approximately 18 months old and again at 24 months of age. Though al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Together, these results suggest that examining internalizing and externalizing symptoms together is appropriate for younger samples. Indeed, although we found no environmental covariance between NE and problem behavior, one study of a high‐risk sample found that an environment characterized by multiple stressors (e.g., neighborhood dangerousness, and overcrowding) exacerbated the relation between toddlers’ NE and internalizing problems (Northerner, Trentacosta, & McLear, ), supporting the idea that relations between NE and more severe behavior problems can be environmentally‐dependent under stress.…”
Section: Discussionsupporting
confidence: 68%
“…Together, these results suggest that examining internalizing and externalizing symptoms together is appropriate for younger samples. Indeed, although we found no environmental covariance between NE and problem behavior, one study of a high‐risk sample found that an environment characterized by multiple stressors (e.g., neighborhood dangerousness, and overcrowding) exacerbated the relation between toddlers’ NE and internalizing problems (Northerner, Trentacosta, & McLear, ), supporting the idea that relations between NE and more severe behavior problems can be environmentally‐dependent under stress.…”
Section: Discussionsupporting
confidence: 68%
“…However, some studies have shown that early emotional negativity may moderate other associations implicating later externalizing behaviors, such as the relation between early child care and externalizing behaviors during adolescence (119). Another study (76) found that low early negative emotionality at 18 months emerged as a protective factor in children experiencing a cumulative risk of developing internalizing and sleep problems at 24 months. Consequently, and in the absence of a concurrent measure of negative emotionality, this long-term effect noted across several studies also supports the hypothesis that negative emotionality is a relatively stable developmental characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is its moderating effect that has been mainly reported in the literature. Indeed, difficultness is already known to moderate relations between a variety of risk factors and children's behavior, such as the associations between cumulative contextual risk and children's externalizing, internalizing, and sleep problems (75)(76)(77)(78). Some early temperamental characteristics may indeed predispose children to develop later behavior problems, particularly when other risk factors are present (79)(80)(81)(82).…”
Section: Introductionmentioning
confidence: 99%
“…A cumulative risk approach is also more parsimonious, has more statistical power, and has no multicollinearity problems (Evans et al., ; Flouri & Kallis, ). Research using a cumulative risk index found that a higher number of risk factors at birth or during early childhood were related to more externalizing problem behavior in young children (Bennett, Marini, Berzenski, Carmody, & Lewis, ; Gassman‐Pines & Yoshikawa, ; Northerner, Trentacosta, & McLear, ; Trentacosta et al., ). These findings support the importance of examining cumulative risk compared with single risk models in relation to early childhood aggression.…”
Section: Introductionmentioning
confidence: 99%